POTENSI DAN KELAYAKAN FINANSIAL USAHA PETERNAKAN SAPI POTONG DI DESA ALEBO KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Hasiruddin Hasiruddin; Harapin Hafid; La Malesi (Universitas Halu Oleo, 2015)
The purpose of this study to determine the potential of seed, feed, land, housing, capital, labor and equipment, and to determine the feasibility fianansial beef cattle breeding business in the Village Alebo District Konda. The population in this study were all breeders of beef cattle, amounting to 142 households with a fixed number of samples studied as much as 30% (47 families) from the existing population. Population breeders for 3 (three) parts, namely: 1) the eastern region, 2) the middle region, and 3) the western region. Determination of the sample with use strafetied proportional random sampling technique. Variables observed are the characteristics of the respondents, the potential for beef cattle breeding business, business expenses, revenues and financial feasibility. To determine the characteristics and potential of beef cattle business in the descriptive analysis and to determine the feasibility of beef cattle breeding business financially in the analysis by the Revenue Cost Ratio analysis (R/C Ratio), Pay Back Period (PBP) and Breack Even Point (BEP). Beef cattle breeding business in the Village Alebo District Konda enough potential to be developed. These conditions can be seen from the availability of seed, feed, land, housing, drugs, capital, labor and equipment beef cattle breeding business. Financial analysis of beef cattle breeding research in the area deserve to be developed. The results obtained by averaging the research conducted by breeders of beef cattle receipts on average Rp. 11,765,958,- total average income Rp. 7,246,035,-, analysis of R/C Ratio obtained by the average value 1.6, the value obtained PBP 0.3 year in which the value of investments shorter than the age of 9.5 years of investment and BEP value of 0.8 (1 tail) with a value of Rp. 2,259,961,-.Key words: Potential, Financial Feasibility, Livestock Farming, Beef CattleABSTRAKTujuan penelitian ini untuk mengetahui potensi bibit, pakan, lahan, kandang, modal, tenaga kerja dan peralatan, dan mengetahui kelayakan fianansial usaha peternakan sapi potong di Desa Alebo Kecamatan Konda. Populasi dalam penelitian ini adalah semua peternak sapi potong yang berjumlah 142 KK dengan jumlah sampel yang diteliti ditetapkan sebannyak 30% (47 KK) dari populasi yang ada. Populasi peternak di bagi 3 (tiga) bagian wilayah yaitu ; 1) Wilayah bagian timur, 2) Wilayah bagian tengah, dan 3) Wilayah bagian barat. Penentuan sampel dengn menggunakan teknik propotional strafetied random sampling. Variabel dalam penelitian ini adalah karakteristik responden, potensi usaha peternakan sapi potong, biaya usaha, pendapatan usaha dan kelayakan finansial. Untuk mengetahui karakteristik dan potensi usaha ternak sapi potong di analisis secara deskriptif serta untuk mengetahui kelayakan finasial usaha peternakan sapi potong digunakan analisis Revenue Cost Ratio (R/C), Pay Back Period (PBP) dan Breack Even Point (BEP). Usaha peternakan sapi potong di Desa Alebo Kecamatan Konda cukup potensi untuk dikembangkan. Kondisi tersebut dapat dilihat dari ketersediaan bibit, pakan, lahan, kandang, obat-obatan, modal, tenaga kerja dan peralatan usaha peternakan sapi potong. Analisis finansial usaha peternakan sapi potong layak untuk dikembangkan. Hasil yang diperoleh rataan penerimaan per peternak sapi potong rata-rata Rp.11,765,958,- total pendapatan rata-rata Rp. 7,246,035,-, analisis R/C Ratio diperoleh nilai rata-rata 1.6, nilai PBP diperoleh 0.3 tahun dimana nilai investasi lebih pendek dari umur investasi 9.5 tahun dan nilai BEP sebesar 0.8 (1 ekor) dengan nilai Rp. 2,259,961,-.Kata Kunci ; Potensi, Kelayakan Finansial, usaha peternakan, Sapi Potong